PEMANFAATAN LIMBAH PETERNAKAN DALAM KONSEP PERTANIAN TERPADU GUNA MEWUJUDKAN PERTANIAN YANG BERKELANJUTAN - Suryono Suryono; Widyatmani Sih Dewi; Sumarno Sumarno (Caraka Tani: Journal of Sustainable Agriculture, 2014)
Utilization of farm wastes in order to realize the concept of integrated farming is a sustainable agriculture community service program in cooperation with two partners, namely : ( 1 ) quail - catfish Breeders 'Agribird', and ( 2 ) dairy farms and agricultural businesses " Andini Mulyo ". This service activities conducted through outreach / awareness, mentoring and manufacture of demonstration plots. Preparation of demonstration plots to make an example of earthworm cultivation ( vermikultur ) and the making of silage. Testing vermicompost and organic fertilizer from cow dung to plant corn and kale using plots measuring 50 x 9 meters, divided into 3 blocks, each 3 x 50 meters. Outcome in the form of products include : Biomass earthworm number 5 Kg / month ; Vermicompost 50 Kg ; Silage, 300 Kg once manufacture ; and quality organic fertilizer from cow dung, 600 kg / process. Outcome in the form of a test product to the plant : the use of manure, vermicompost fertilizer in Litosol very real increase maize crop which includes fresh weight of corn stover, corn stover dry weight and dry weight of seed corn ; the use of manure and fertilizer plants in the ground grumosol not significantly different with kale stover fresh weight, while the use of vermicompost highly significant increase stover fresh weight of spinach.